PENERAPAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) DALAM EVALUASI KUALITAS WEBSITE KOMUNITAS KUMPULAN WARGI SUKAPURA (KWS) - Leviana, Rika; Rahmatulloh, Alam (Universitas Trunojoyo Madura, 2024)
One use of websites is applied in a community, namely the Sukapura Wargi Group, where in this community it is used as a medium for conveying information and managing data. The new KWS website was created because previously it did not have any website. A website must have good quality, because website quality is an important factor that must be considered so that it has good value in cyberspace and can be used as expected. To measure the quality of the KWS website, it is necessary to carry out an evaluation to ensure an optimal experience for users. The methods that can be used to evaluate the quality of community websites are the WebQual 4.0 method and Importance Performance Analysis (IPA). The application of the WebQual 4.0 method is because it can measure website quality based on three main dimensions, namely information quality, interaction quality and service quality. Meanwhile, the natural science method is used as a calculation method. The results of this research show that the KWS community websites that have been measured have an average value of Performance and Importance of 9.082 and 10.48. The average result obtained based on the suitability level value is 93.15% with the largest suitability level value found in the usability dimension, namely 100.82%, while the result of the average gap value (GAP) is -3.079.Keywords: Importance Performance Analysis, Kumpulan Wargi Sukapura, Website, WebQual